Efficacy and Safety of Mirvetuximab Soravtansine in Patients With Platinum-Resistant Ovarian Cancer With High Folate Receptor Alpha Expression: Results From the SORAYA Study - Matulonis, Ursula A.; Lorusso, Domenica; Oaknin, Ana; Pignata, Sandro; Dean, Andrew; Denys, Hannelore; Colombo, Nicoletta; Van Gorp, Toon; Konner, Jason A.; Marin, Margarita Romeo; Harter, Philipp; Murphy, Conleth G.; et al. (Journal of clinical oncology, 2023)
PURPOSESingle-agent chemotherapies have limited activity and considerable toxicity in patients with platinum-resistant epithelial ovarian cancer (PROC). Mirvetuximab soravtansine (MIRV) is an antibody-drug conjugate targeting folate receptor α (FRα). SORAYA is a single-arm, phase II study evaluating efficacy and safety of MIRV in patients with PROC.METHODSSORAYA enrolled FRα-high patients with PROC who had received one to three prior therapies, including required bevacizumab. The primary end point was confirmed objective response rate (ORR) by investigator; duration of response was the key secondary end point.RESULTSOne hundred six patients were enrolled; 105 were evaluable for efficacy. All patients had received prior bevacizumab, 51% had three prior lines of therapy, and 48% received a prior poly ADP-ribose polymerase inhibitor. Median follow-up was 13.4 months. ORR was 32.4% (95% CI, 23.6 to 42.2), including five complete and 29 partial responses. The median duration of response was 6.9 months (95% CI, 5.6 to 9.7). In patients with one to two priors, the ORR by investigator was 35.3% (95% CI, 22.4 to 49.9) and in patients with three priors was 30.2% (95% CI, 18.3 to 44.3). The ORR by investigator was 38.0% (95% CI, 24.7 to 52.8) in patients with prior poly ADP-ribose polymerase inhibitor exposure and 27.5% (95% CI, 15.9 to 41.7) in those without. The most common treatment-related adverse events (all grade and grade 3-4) were blurred vision (41% and 6%), keratopathy (29% and 9%), and nausea (29% and 0%). Treatment-related adverse events led to dose delays, reductions, and discontinuations in 33%, 20%, and 9% of patients, respectively.CONCLUSIONMIRV demonstrated consistent clinically meaningful antitumor activity and favorable tolerability and safety in patients with FRα-high PROC who had received up to three prior therapies, including bevacizumab, representing an important advance for this biomarker-selected population.